A window into the Great Unconformity: Insights from geochemistry and geochronology of Ediacaran glaciogenic rocks in the North China Craton. (1st June 2020) - Li, Meng; Vandyk, Thomas Matthew; Wu, Guanghui; Liu, Wei; Le Heron, Daniel Paul; Xiao, Yang
Graphical abstract: Highlights: Great Unconformity investigated using glaciogenic strata. Whole rock compositions are used as proxy for Ediacaran Upper Continental Crust. Glacial abrasion created of accommodation space. Abstract: The "Great Unconformity" across the Proterozoic-Phanerozoic boundary has long been recognised as critical for understandings of the Cambrian Explosion and changes in sediment preservation. However in many parts of the Earth no rock strata are preserved for hundreds of millions of years leading up to the Cambrian Period. This study reports detrital zircon age and whole rock geochemical data from 43 samples of glaciogenic rocks in the Ediacaran Luoquan and Dongpo Formations. Detrital zircon age populations show a distinct peak at ca. 2.5 Ga and minor peaks at 2.2–1.6 Ga, typical of Mesoproterozoic provenance. It has been established that glaciogenic strata are uniquely suited as a proxy for the average upper continental crust (UCC). Applying this principle, the samples presented herein are used to provide insights into the UCC present in the North China Craton (NCC) during the Great Unconformity. This reveals UCC older than the Neoproterozoic but younger than the Great Oxygenation Event. Based upon these findings a tectonic and climatic model is proposed, using a modern analogue from Antarctica, wherein accommodation space was created by glacial abrasion whilst uplift continued throughout the NCC. This overdeepening process provides an explanation for the preservation of these glaciogenic strata, despite the Great Unconformity that surrounds them on all sides and this study contribute towards understanding of processes in the NCC during a critical time when little has survived into the rock record.